Assessing and Analyzing Natural Land Cover Degradation in North Kordofan State Using GIS and RS - Eltom, Ibrahim Mohamed; Maryoud, Amna Mohammed Bashir (Journal of natural sciences, life and applied sciences, 2022)
The modern land environmental degradation in Sudan was started prominently after the severe drought in 1984, when all socioeconomic sectors and environmental settings were affected by severe drought. The main objective of this paper is to assess the most observed and measured types of degradation over the North Kordofan State in Western Sudan using different spatial analysis techniques and remote sensed data. Data used are from different sources include satellite imageries, Google Earth and field-based observation and meetings methods. The data analyzed using ArcGIS 10.4 and Erdas Imagine 2014 softwares for processing the data. NDVI spectral index has been used for assessing the land cover greenings. The results presented by maps showed the severe degradation surrounding villages and towns. The results quantification showed that the study area exposed to severe degradation since 1984, and he most affected areas are surrounding towns that 100% of the deforestation was depicted surrounding ElObeid city. Village deforestation was evaluated to be more than 45% of the sampled villages using buffer analysis estimation. During drought seasons in 1984 and 1990, NDVI results showed negative values that indicated about 89% of land were degraded seasonally (less greenings cover) used to assess situ land degradation in the study area.